1997
DOI: 10.1002/art.1780401207
|View full text |Cite
|
Sign up to set email alerts
|

Oncostatin M stimulates monocyte chemoattractant protein‐1‐ and interleukin‐1‐induced matrix metalloproteinase‐1 production by human synovial fibroblasts in vitro

Abstract: Objective. To measure levels of oncostatin M (OSM) in the synovial fluid of rheumatoid arthritis (FU) patients and to examine the activities of human OSM in the regulation of human synovial fibroblast (HSF) production of chemokines and matrix metalloproteinases (MMP-1 and MMP-3) in vitro.Methods. We examined the levels of OSM in the synovial fluids of patients with arthritis by an enzymelinked immunosorbent assay (ELISA). ELISA of cell culture supernatants and Northern blots were used to assess responses of HS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
70
1

Year Published

1998
1998
2011
2011

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(76 citation statements)
references
References 48 publications
5
70
1
Order By: Relevance
“…So far, most studies corroborating the involvement of OSM in the development and progression of RA have highlighted its contribution to cartilage breakdown preferentially by up-regulation of MMPs and aggrecanases (18,20,22,26,46) as well as changes in the MMP:TIMP ratio in favor of MMPs (19,37). In this study, we identified OSM as the main regulator of CCL13 chemokine expression by SFs.…”
Section: Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…So far, most studies corroborating the involvement of OSM in the development and progression of RA have highlighted its contribution to cartilage breakdown preferentially by up-regulation of MMPs and aggrecanases (18,20,22,26,46) as well as changes in the MMP:TIMP ratio in favor of MMPs (19,37). In this study, we identified OSM as the main regulator of CCL13 chemokine expression by SFs.…”
Section: Discussionsupporting
confidence: 52%
“…In vitro, OSM modulates matrix turnover in synoviocytes, chondrocytes, and cartilage explants, suggesting a pivotal role for OSM in the regulation of the balance between matrix metalloproteinases (MMPs) and tissue inhibitors of matrix metalloproteinases (TIMPs) at sites of destruction (20,(22)(23)(24). In addition, OSM has been demonstrated to act synergistically with proinflammatory cytokines such as IL-1␤, TNF␣, and IL-17 to induce extracellular matrix turnover (20,25,26).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However in progressive chronic conditions OSM concentrations are more sustained and originate from activated macrophages and T lymphocytes (7,9). Such differences in OSM expression may have a considerable bearing on the inflammatory response since OSM synergizes with other inflammatory mediators including IL-1, TNF-␣, IL-6, IL-17, and IFN-␥ to affect degradation of extracellular matrix, leukocyte recruitment, and wound healing (16,20,21,32,33). However, based on OSM reconstitution studies in experimental models of disease, it is difficult to gauge whether OSM directs a protective or detrimental outcome in vivo (5,6,9,34,35).…”
Section: Discussionmentioning
confidence: 99%
“…Besides tumor necrosis factor ␣ (TNF␣) and interleukin-1 (IL-1)-family cytokines, there is increasing evidence that IL-6 family members and signaling pathways downstream of the common gp130 receptor subunit are important in the pathogenesis of both murine and human inflammatory arthritis (2). Oncostatin M (OSM) is a member of the IL-6 family, and many studies have demonstrated that it has a stimulatory role in the progression of RA (3,4). In a previous study, we demonstrated that OSM induced strong expression of CCL2, a potent chemoattractant for monocyte/macrophages, in human osteoblastic cells, at both the messenger RNA (mRNA) and protein levels (5), supporting the notion that OSM and osteoblasts have an important role in the mediation of inflammatory bone diseases.…”
mentioning
confidence: 99%